Loading of a Coordination Polymer Nanobelt on a Functional Carbon Fiber: A Feasible Strategy for Visible‐Light‐Active and Highly Efficient Coordination‐Polymer‐Based Photocatalysts. Issue 9 (13th January 2015) - Xu, Xin‐Xin; Yang, Hong‐Yu; Li, Zhen‐Yu; Liu, Xiao‐Xia; Wang, Xiu‐Li
Abstract To improve the photocatalytic properties of coordination polymers under irradiation in the visible‐light region, coordination polymer nanobelts (CPNB) were loaded on functional carbon fiber (FCF) through the use of a simple colloidal blending process. The resulting coordination polymer nanobelt loaded functional carbon fiber composite material (CPNB/FCF) exhibited dramatically improved photocatalytic activity for the degradation of rhodamine B (RhB) under visible‐light irradiation. Optical and electrochemical methods illustrated the enhanced photocatalytic activity of CPNB/FCF originated from high separation efficiency of photogenerated electrons and holes on the interface of CPNB and FCF, which was produced by the synergy effect between them. In the composite material, the role of FCF could be described as photosensitizer and good electron transporter. For FCF, the number of functional groups on its surface has a significant influence on the photocatalytic performance of the resulting CPNB/FCF composite material, and an ideal FCF carrier was obtained as a highly efficient CPNB/FCF photocatalyst. CPNB/FCF showed outstanding stability during the degradation of rhodamine B (RhB); thus, the material is suitable for use as a photocatalyst in the treatment of organic dyes in water.